Tourist Perception To Hatten Wine Product As Part Of Balinese Culinary Art - Rais, Syafruddin (Universitas Pelita Harapan Medan, 2017)
Bali as a tourist destination has abundant culture and art attractions such as dances, music, painting, sculpture and culinary arts. Culinary arts is well known for a longtime as part of gastronomy. Wine in Indonesia is dominated by import products but there is a local wine which has a similar quality and the name is hatten wines. This wine has been produced since 1994Â using a local grape from Indonesia which is the type alphonse lavallee.The purpose for this research is to identify the potency of Hatten wine products as Bali culinary, tourist perception of Hatten Wine, and how to improve the quality of Hatten Bali as part of Â Balinese gastronomy. This research has been done in The Hatten Wine factory and 5 bars and restaurants located in Bali Hyatt Nusa Dua, Sanur Hyatt Hotel, Bali Intercontinental, Hard Rock and Ayana Resort and Spa. As an informant of this research is the management of Hatten Wine and the respondent is tourists that visited the 5 bars and restaurants in each place there were 20 respondents and the total respondents were 100 by using accidental random sampling technique.Analysis shows the indication that Hatten Wine product has been an interest to the foreigners. 70 % of respondent said that Hatten Wine as their souvenir, 60 % of respondent said the quality of the product is very good, 62 % of respondent said that the combination between Hatten Wine product with Balinese cuisine is very good and 60 % of respondent said that the combination between Hatten Wine product with foreign culinary is very good. An effort to improve the quality of Hatten Wine are improving the quality of human resources, promoting the product by providing direct relationship with hotels and restaurants. The conclusion from this research is the foreigners love Hatten Wine productÂ and enjoying Bali culinary art.